An exploration of the educational experiences of new nurses who are men within Aotearoa New Zealand : a thesis presented in partial fulfilment of the requirements for the degree of Master of Health Science in Nursing at Massey University, Manawatu, New Zealand - Guy, Max Timothy (Massey University, 2020)
Despite worldwide efforts to recruit more men into nursing, males still hold minority status within the profession, which is unsustainable for many reasons. For one, a projected health crisis looms due to the baby boomer generation facing retirement by 2035. This section of the population will require more nursing care due to an increased life expectancy with more complex health needs. To compound this problem, many of those who will be retiring are nurses themselves. New Zealand subsequently faces an increased demand for nursing care, underscored by a critical nursing shortage. Ideally, it is here that males should be available to fill this shortage, as they constitute half the population. However, men presently make up only 9% of the New Zealand nursing workforce, a figure mostly unchanged since the 1990s. Men may be unwilling to enter a career in nursing due to societal attitudes, stigma, media representations, and the ingrained feminine construct of nursing. Consequently, this leaves an untapped pool of potential nurses who could help meet the demand of predicted population demographics. Using a descriptive qualitative design underpinned by social constructionism, this study explored the experiences of male nurses prior, during and after the Bachelor of Nursing degree. This research aimed to inform future curriculum design to support, retain, and attract more New Zealand men to nursing. Nine participants from across New Zealand provided data via semi-structured interviews. Through thematic analysis, two overarching themes surfaced. Firstly, men often feel a sense of isolation during training that is perceived as unfavourable, but not without benefits. Secondly, participants saw that an inaccurate awareness of the scope of the modern nurse remains constructed within the public consciousness. Addressing both of these themes is imperative to ensure balanced gender diversity within nursing, but to also empower nursing as a whole.
Keywords: 420599 Nursing not elsewhere classified